162k views
2 votes
Prove the identity.cot x (sec^2x-1)= tan x

1 Answer

3 votes

cot\text{ }x(sec^2x-1)=tan\text{ }x

Using one of the Pythagorean Identities, we can replace sec²x with 1 + tan²x. The equation above becomes:


cot\text{ }x(1+tan^2x-1)=tan\text{ }x

Applying Algebra, we can add the terms 1 and -1 in the parenthesis. The equation becomes:


cot\text{ }x(tan^2x)=tan\text{ }x

Applying the reciprocal of cot x, we can replace cot x with 1/tan x.


((1)/(tanx))(tan^2x)=tanx

Divide tan²x by tan x and the quotient is:


tan\text{ }x=tan\text{ }x

As we can see above, the left side of the equation has been proven to be equal to its right side. Hence, the trigonometric equation is an identity.

User Malte Schwerhoff
by
5.0k points